Cell-based high-throughput compound screening reveals functional interaction between oncofetal HMGA2 and topoisomerase I - Peter, Sabrina (2018)
HMGA2 is an important chromatin factor that interacts with DNA via three AT-hook domains, thereby regulating chromatin architecture and transcription during embryonic and fetal development. The protein is absent from differentiated somatic cells, but aberrantly re-expressed in most aggressive human neoplasias where it is causally linked to cell transformation and metastasis. DNA-binding also enables HMGA2 to protect cancer cells from DNA-damaging agents. HMGA2 therefore is considered to be a prime drug target for many aggressive malignancies. Here, we have developed a broadly applicable cell-based reporter system which can identify HMGA2 antagonists targeting functionally important protein domains, as validated with the known AT-hook competitor netropsin. In addition, high-throughput screening can uncover functional links between HMGA2 and cellular factors important for cell transformation. This is demonstrated with the discovery that HMGA2 potentiates the clinically important topoisomerase I inhibitor irinotecan/SN-38 in trapping the enzyme in covalent DNA-complexes, thereby attenuating transcription.